Junior high school students' risk perception of earthquakes in Bandung City. Issue 1 (May 2021) - Saepulloh, A; Siahaan, P; Widodo, A; Suhendi, E
Abstract: This study aims to determine students' risk perceptions of earthquakes of junior high school students in Bandung City and whether factors such as gender, school location and school status affect their risk perceptions of earthquakes. A questionnaire on risk perceptions was given to 128 junior high school students in six schools in Bandung City. Based on data analysis using the independent t-test, there is a significant difference in risk perception between male and female students where female students (73.48) have a higher average risk perception score than male students (70.50). However, school location and school status do not affect risk perceptions since the results of the independent t-test showed no significant difference. This is because both are external factors, while the perception of risk is influenced by internal factors. In addition, among the risk perception components, the perception component towards disaster risk reduction has the highest value and the perception component toward risk potential has the lowest value. This indicates that the perception component towards disaster risk reduction gave the greatest contribution to the risk perception and junior high school students in Bandung City need to increase their risk perception of potential earthquakes.